Maksimalisasi Kemampuan Pemecahan Masalah Matematika melalui Penerapan Model PBL pada Siswa SD - Hatmoko, Fajar Tri; Wahyuni, Nur; Shahidayanti, Tutik; Siswanto, Deny Hadi (Prodi PGMI STAI Sabili Bandung, 2025)
Mathematics education in elementary schools plays an important role in developing students' logical and analytical thinking skills, but many still experience difficulties in understanding and solving mathematics problems that require critical thinking. This research aims to analyze the effectiveness of the Problem Based Learning (PBL) model in improving the mathematical problem solving abilities of fifth grade students at SD Muhammadiyah Mlangi. The method used is the Kemmis and McTaggart model of classroom action research, including planning, implementation, observation and reflection. The research subjects consisted of 27 class V students. Data was collected through evaluation tests and observation of student activities in PBL-based learning, then analyzed comparatively descriptively. The research results show that the application of PBL has a positive impact on students' problem solving abilities. The average value increased from 65.87 in the pre-cycle to 77.95 in Cycle I and 86.44 in Cycle II. Students also become more active and confident in solving math problems. These findings indicate that PBL is effective as an innovative learning strategy in improving the quality of mathematics learning in elementary schools